PELATIHAN MANASIK HAJI SEBAGAI STRATEGI DAKWAH EDUKATIF BAGI SISWA SD EL-YAMIEN SEMANDING TUBAN - Fitriana Wahyu Lestari, Siti Kris; Jabbar, Mohammad Abdul (CV. Kalimasada Group, 2025)
This study aims to explore and analyze the implementation of Hajj simulation training as an educational da'wah strategy within the context of Islamic primary education at El-Yamien Elementary School, Semanding, Tuban. The research employs the Participatory Action Research (PAR) approach, which emphasizes active and collaborative participation from all educational stakeholders, including students, teachers, and school administrators, in planning, executing, evaluating, and reflecting upon the training activities. The study was conducted in three cycles, each comprising the stages of planning, action, observation, and reflection. Data were collected through direct observation, in-depth interviews, and documentation of the training sessions. The findings indicate that the Hajj training significantly enhanced students’ cognitive understanding of the rituals and procedural aspects of the Hajj pilgrimage. Furthermore, the training fostered the development of students’ religious character through the internalization of Islamic values such as discipline, social awareness, responsibility, and spirituality. The educational da'wah strategy utilizing experiential learning methods proved to be effective in creating a contextual, meaningful, and transformative learning environment. Consequently, Hajj simulation training can serve as a practical and relevant model of da'wah-oriented education applicable within Islamic studies at the primary school level.